"Not a lot of benefits, but you can survive”, the role of technology in micro business resilience during the Covid-19 pandemic - Diah Gandoriah; Eka Siskawati; Zahara; Oladokun Nafiu Olaniyi (Entrepreneurship and Small Business Research, 2022)
The existence of the Indonesian MSME group is recognized as the backbone of national economic development. However, the limited resources of MSME actors are a challenge for MSME actors in adjusting to environmental changes and adapting to the digital technology used. Therefore, this study aims to see and explore the acceptance model of digital technology in the resilience of micro-enterprises in the city of Padang. This research is a non-positivism research with a phenomenological design. The object of this research is micro-enterprises in the city of Padang, selected purposively with snowball sampling. Data was collected by means of in-depth interviews and naturalistic observations. The results of this study found that digital technology helps micro-enterprises to survive during the COVID-19 pandemic. In addition, the cost of implementing the technology tends to be more economical. The use of technology is able to create a wider target market. This research provides an understanding of the role of digital technology in maintaining the resilience of micro-enterprises during the COVID-19 pandemic.